Corporate leverage and the effects of monetary policy on investment: A reconciliation of micro and macro elasticities - Valentin Grob; Gabriel Züllig (University of Neuchâtel, Institute of Economic Research (IRENE), 2024)
We investigate how the level of corporate leverage affects firms' investment response to monetary policy shocks. Based on novel aggregate time series estimates, leverage acts amplifying, whereas in the cross section of firms, higher leverage predicts a muted response to monetary policy. We use a heterogeneous firm model to show that in general equilibrium, both empirical findings can be true at the same time: When the average firm has lower leverage and therefore reduces its investment demand more strongly after a contractionary shock, the price of capital declines sharply, which incentivizes all firms regardless of their leverage to invest relatively more, muting the aggregate decline of investment. We provide empirical evidence supporting this hypothesis. Overall, if there are general equilibrium adjustments to shocks, effects estimated by exploiting cross-sectional heterogeneity in micro data can differ substantially from the macroeconomic elasticities, in our example even in terms of their sign.
Keywords: D22; E32; E44; E52; 330; firm heterogeneity; state dependence; financial frictions; general equilibrium